Quality of life and emotional distress among caregivers of patients newly diagnosed with cancer: Understanding trajectories across the first year post-diagnosis. Issue 5 (2nd September 2020) - Peh, Chao Xu; Liu, Jianlin; Mahendran, Rathi
Abstract: Purpose: The cancer caregiving experience is multifaceted and dynamic across different phases of the cancer care continuum. This longitudinal study examined the trajectories of CQOL and caregiver emotional distress across the first year post-diagnosis. Methods: Participants were 111 caregivers of newly diagnosed patients who completed baseline, 6-month, and 12-month follow-ups. Trajectories of CQOL, CQOL domains, caregiver depression, anxiety, and stress, were estimated using linear and quadratic mixed models. Results: The trajectory of overall CQOL followed an inverse U-shape trend, while caregiver depression, anxiety, and stress remained stable. For CQOL domains, physical/practical needs followed a gradual trend of improvement, while social support followed an inverse U-shape trend; caregiver burden, emotional reactivity, and responsibility/duty remained stable. Conclusions: The multidimensional needs of caregivers of newly diagnosed patients appeared to follow different trajectories across the first year post-diagnosis. While most CQOL domains remained stable, caregivers may experience adjustment difficulties in terms of relational concerns and social support.